Protocol for developing sub-national nutrition scorecards, a tool to advance accountability for nutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The paper describes the protocol for how to develop sub-national scorecards. The National Nutrition Scorecard was shared with senior Government officials, in a workshop co-hosted by the Institute of Development Studies (IDS). Officials discussed potential of using this for social accountability and other aspects of the political economy for nutrition.